ГИПОКИНЕЗИЯ ҲОЛАТИНИНГ КЕЛИБ ЧИҚИШИ ВА ОДАМ ОРГАНИЗМИГА УМУМИЙ ТАЪСИРИ (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Hypokinesia (slowing of movement activity) is noted pathological Morpho–functional changes in tissue cells of various organs in the body. Under the influence of restriction of functional activity of the skeletal muscles of the thigh, hypokinetic syndrome develops.